Salivary gland development in Drosophila melanogaster. - Andrew, D.J.; Henderson, K.D.; Seshaiah, P. (Mechanisms of Development, 2000)
The Drosophila salivary gland is proving to be an excellent experimental system for understanding how cells commit to specific developmental programs and, once committed, how cells implement such decisions. Through genetic studies, the factors that determine where salivary glands will form, the number of cells committed to a salivary gland fate, and the distinction between the two major cell types (secretory cells and duct cells) have been discovered. Within the next few years, we will learn the molecular details of the interactions among the salivary gland regulators and salivary gland target genes. We will also learn how the early-expressed salivary gland genes coordinate their activities to mediate the morphogenetic movements required to form the salivary gland and the changes in cell physiology required for high secretory activity.